Gestión comunicacional y su incidencia en el posicionamiento del público objetivo de la empresa Lonazacorp web solutions de la ciudad de Quevedo, año 2016 - López Holguin, Abraham Alfredo (2016)
The research titled communication management and its impact on the positioning of the target audience of the Lonazacorp Web Solutions Company of the city of Quevedo in 2016 is notorious the low results in the capture of the clients, aiming to analyze the current situation of the processes In addition to determining the influence of the advertising image on the knowledge that the users or clients have to the business and to propose communication strategies for the company in order to improve the positioning in the market. The methodology used in the development of the work was field and bibliographical - documentary, applying the methods of inductive, deductive and analytical research, in addition a population was established according to the data provided by the Chamber of Commerce of Quevedo that until the year 2016 There are 2364 companies, micro-companies and professional people that can buy the services of the business, helping to obtain as a conclusion 95% do not know the brand, also supports the idea of improving the corporate image presented by the business, proposing various options for the establishment Of the name and it was verified that the name of greater acceptance with a 77% Webproject hosting incentive to the design of the manual of corporate identity for the company, it was recommended that the company establishes a planning for the management of the communicational management, determining budgets, strategies And actions that must be taken to position the brand in the target audience.